Therapeutic Potential of Iron Chelators in Viral Diseases: A Systematic Review - Lori, Maryam S.; Khandani, Azade Kalantari; Dehghannoudeh, Gholamreza; Ohadi, Mandana; Ansari, Mehdi (Current Medicinal Chemistry, 2024)
Background: Iron chelators (ICs) have recently emerged as one of the new methods of treatment for viral infections. This study aimed to evaluate the efficiency and safety of natural ICs compared to synthetic ICs. Natural and synthetic ICs are the most common therapeutic agents tested for the treatment of viral infections. When evaluated against synthetic ICs, natural ICs are probably favored owing to their lower toxicity and safer properties. The main objective of the present systematic review was to assess the current evidence on the role of pharmacological mechanisms in the treatment of viral infections. Methods: This study was designed as a systematic review in which search strategies were focused on two electronic databases, PubMed, and Scopus, between 2017 and 2021. A search filter with two subjects, “iron chelators” and “viral infection”, was employed. Results: According to the results, both natural and synthetic chelators had a considerable impact on the treatment of viral infections via various mechanisms, with natural ICs being the most extensively used. Conclusion: Natural and synthetic ICs exert their effects through different pharmacological mechanisms. Among these compounds, natural chelators are more widely used due to their safety, efficacy, and a wider range of applications.
Keywords: mechanisms